VOLTAGE-CONTROLLED GENERATOR - BALYKO IL'JA ALEKSANDROVICH; BALYKO ALEKSANDR KARPOVICH; MJAKIN'KOV VITALIJ JUR'EVICH; SAVEL'EVA LJUDMILA GENNAD'EVNA (2015)
FIELD: oil and gas industry.SUBSTANCE: in the generator there is an additional Schottky-barrier field-effect transistor - the third one, two inductance coils - the second and third ones, a coupling capacitor and a low-frequency power supply filter, at that the drain of the third Schottky-barrier field-effect transistor is connected to a power transmission line at the output through the coupling capacitor and simultaneously to the drain of the second Schottky-barrier field-effect transistor through the second inductance coil, the gate of the third Schottky-barrier field-effect transistor is connected to the source of the second Schottky-barrier field-effect transistor, and their common point of connection is grounded through the third inductance coil, the source of the third Schottky-barrier field-effect transistor is grounded, while to the drain of the second Schottky-barrier field-effect transistor voltage of a positive polarity is fed through the low-frequency power supply filter, at that the value of the third inductance coil is five times less than the value of the second inductance coil and capacitance value of the coupling capacitor is defined by a specified expression.EFFECT: expanding the range of frequency tuning at the preservation of the lower limit of the frequency range and potential development of the generator in a monolithic form.3 dwg Изобретение относится к генераторам управляемым напряжением. Технический результат заключается в расширении диапазона перестройки частоты при сохранении нижнего предела диапазона частот и возможности создания генератора в монолитном исполнении. В генератор дополнительно введены полевой транзистор с барьером Шотки - третий, две индуктивности - вторая и третья, разделительный конденсатор и низкочастотный фильтр питания, при этом сток третьего полевого транзистора с барьером Шотки соединен с линией передачи на выходе через разделительный конденсатор и одновременно - со стоком второго полевого транзистора с барьером Шотки через вторую индуктивность, затвор третьего полевого транзистора с барьером Шотки соединен с истоком второго полевого транзистора с барьером Шотки, и их общая точка соединения заземлена через третью индуктивность, исток третьего полевого транзистора с барьером Шотки заземлен, а на сток второго полевого транзистора с барьером Шотки подают постоянное напряжение положительной полярности через низкочастотный фильтр питания, при этом величина третьей индуктивности в пять раз меньше величины второй индуктивности, а величину емкости разделительного конденсатора определяют из определенного выражения. 3 ил.